Unit-level models and discrete demand - Allenby, Greg M. (Henry Stewart Talks, 2010)
Economic models, Logit and probit models, Linear utility, contours and budget, Choice probabilities, Multinomial probit models, Differenced system, Conditional normal distribution, Identification issues, Superior and normal goods, Displacement parameters, Kuhn-Tucker conditions for satiation, Estimating the multivariate probit model, Component loadings